Female stone sculptures in the cultural landscape of Kazakhstan (Journal of Philosophy Culture and Political Science, 2026)
This article provides a scholarly examination of anthropomorphic stone statues with female features found in Kazakhstan’s cultural landscape. The main objective of the study is to identify the semantic, historical, and cultural characteristics of female stone sculptures created during ancient and medieval periods. By analyzing the spatial distribution and function of these artifacts within the context of nomadic culture formation, the authors reveal their sacred meaning and social significance. The object of this study is stone sculptures of anthropomorphic women in Kazakhstan. The subject of the research is the figurative features of these sculptures, their spatial arrangement, and their place in the historical context.The article presents an extensive registry of female statues based on archaeological and ethnographic data. The research methodology includes historical-comparative, archaeological-typological, and cultural analysis approaches. The study offers concrete evidence of the connection between female stone statues and the cult of the mother, fertility, and the sacred status of women in ancient Kazakh society. This research enables a deeper understanding of the spiritual worldview of nomadic communities and contributes significantly to the systematization of Kazakh cultural heritage. The registry and analyses proposed by the authors also clarify the role of female statues in contemporary pilgrimage practices. The article’s findings have practical applications in scientific research and museum work in the fields of ethnography and cultural studies.Keywords: female stone statues, badiz, balbal, cultural landscape, ethnography